Distribution of rDNA and polyploidy in Deschampsia antarctica E. Desv. in Antartic and Patagonic populations - González, María Laura; Urdampilleta, Juan Domingo; Fasanella, Mariana; Premoli Il'grande, Andrea Cecilia; Chiapella, Jorge Oscar (Polar Biology)
Unlike the Arctic flora, with many floweringplant species offering opportunities to study evolutionaryprocesses, the Antarctic flora offers only two. One of themis the Antarctic grass Deschampsia antarctica E. Desv.,whose distribution spans from northern Patagonia (ca.38S) down to Alamode Island (ca. 68S), in the west sideof the Antarctic Peninsula. While some aspects of Antarcticplants have been extensively studied (e.g., anatomy,physiology, genetics), little is known about the relatedPatagonian populations. Particularly in cytogenetics, nosingle study has focused on continental populations and itsrelationships with the Antarctic plants. The combination oftraditional fluorescent in situ hybridization (FISH) with aphylogenetic framework highlights the importance ofcytogenetics in plant evolutionary studies, by allowingcomparison of chromosome characters in phylogeneticallyrelated individuals. Most used characters for this purposeare the chromosome number, karyotype morphology andpatterns of repetitive DNA. These were used to comparedistant populations of D. antarctica in a phylogeneticframework, to obtain a first view of the cytogeneticstructure of the species along its distribution. Patagonianpopulations have greater variability in the chromosomaland molecular characters, while Antarctic populations arevery alike, hinting at a South American origin hypothesis.A polyploid population is reported for the first time,located on Central Patagonia populations, close to thenorthern limit of distribution range. Cytogenetic characteristicssuggest that hybridization processes could haveplayed an important role in the evolution of the genome ofD. antarctica. Fil: González, María Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto Multidisciplinario de Biología Vegetal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto Multidisciplinario de Biología Vegetal; Argentina Fil: Urdampilleta, Juan Domingo. ...